2012
DOI: 10.7742/jksr.2012.6.6.521
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Kager's Triangle Area and Retrocalcaneal Surface Temperature by shoes heel height

Abstract: The aim of this study was to analyze radiological change of Kager's triangle area and retrocalcaneal surface temperature by shoes heel height. Area of Kager's triangle was measured by simple radiography study And PACS of INFINITI. Retrocalcaneal surface temperature were measured by DITI. Area of Kager's triangle and retrocalcaneal surface temperature were calculated for comparison and analysis, with flat shoes and high heel shoes. Area of Kager's triangle(0.88cm²) and retrocalcaneal surface temperature (1.4℃)t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…The difference with the results of the study by Jeon et al is due to the fact that our study was conducted on embalmed cadavers, and the ankles of the cadavers were fixed in planta flexion due to the effect of gravity. Plantar flexion also reduces the area of the Kager fat pad (14).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The difference with the results of the study by Jeon et al is due to the fact that our study was conducted on embalmed cadavers, and the ankles of the cadavers were fixed in planta flexion due to the effect of gravity. Plantar flexion also reduces the area of the Kager fat pad (14).…”
Section: Methodsmentioning
confidence: 97%
“…In the literature, 2 studies were found in which the area of the Kager's triangle was examined. was determined that the Kager region shrank in the subjects wearing high heels, and the shape of the Achilles tendon and Kager's triangle changed (14).…”
Section: Methodsmentioning
confidence: 99%